Research and evaluation of sparse array for massive MIMO - Mengting LOU; Jing JIN; Hanning WANG; Qixing WANG; Jiangzhou WANG (Dianxin kexue)
Massive multiple-input multiple-output (mMIMO) enables higher spectrum efficiency by deploying a large number of antenna elements.However, mMIMO will bring a substantial increase in the number of radio frequency (RF) channel, which will result in a sharp increase in cost.Therefore, it is necessary to design mMIMO with comprehensive consideration of the trade-off between the performance and the cost.Sparse array technology can approach the performance of the uniform array with less number of antenna elements by optimizing the position distribution and excitation amplitudes of the antenna elements, thereby reducing the number of RF channels and controlling the cost, and achieving a better cost-effective balance.Both link-level and system-level evaluations and analysis of sparse array based mMIMO that targets for 6G were performed under realistic simulation settings.The results show that with little performance loss, the sparse array based mMIMO can significantly reduce the number of antenna elements and the cost of base station infrastructure.